# How do you find the derivative of #g(t)=e^(-3/t^2)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To find the derivative of ( g(t) = e^{-3/t^2} ), we can use the chain rule. The chain rule states that if ( f(x) ) and ( g(x) ) are differentiable functions, then the derivative of the composition ( f(g(x)) ) is given by ( f'(g(x)) \cdot g'(x) ).

In our case, ( f(x) = e^x ) and ( g(x) = -3/x^2 ). So, ( f'(x) = e^x ) and ( g'(x) = 6/x^3 ).

Now applying the chain rule, we have:

[ g'(t) = f'(g(t)) \cdot g'(t) = e^{-3/t^2} \cdot \left(\frac{d}{dt} \left(-\frac{3}{t^2}\right)\right) ]

[ g'(t) = e^{-3/t^2} \cdot \left(\frac{6}{t^3}\right) = \frac{6}{t^3} \cdot e^{-3/t^2} ]

So, the derivative of ( g(t) ) with respect to ( t ) is ( \frac{6}{t^3} \cdot e^{-3/t^2} ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the derivative of #ln(x^2-4)#?
- How do you find the first and second derivative of #y=1/(1+e^-x)#?
- How do you differentiate f(x)=#1/sqrt(x-4)# using first principles?
- How do you find the derivative of #y=[e^(-2x)][1 + e^(-2x)]^(-1/2)#?
- How do you find the derivative of #y=e^x(sinx+cosx)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7